Diseño conceptual de una solución para la recolección y aprovechamiento de residuos sólidos flotantes en una porción del Rio Magdalena, adaptada a una embarcación turística (2023)
MagdaSolids aims to address one of the most critical issues in the Rio Magdalena: pollution from suspended solid waste. This pollution disrupts navigability, public health, well-being, and tourism in Barranquilla, while also impacting the local fauna and flora. To tackle this problem, a field analysis was conducted to devise a design concept for collecting and utilizing floating solid waste along a stretch of the Rio Magdalena. The methodology involved researching the design of a tool or structure to be used on a vessel. Four alternatives were proposed to create an optimal waste collection system, enabling the vessel to effectively navigate the tour route established by MagdaTours. Field data from the usual route of the Golfo de Morrosquillo II and relevant information about the river and the vessel, obtained from various databases provided by IDEAM, Uninorte, and DIMAR, were utilized. Different elements were quoted for cost optimization during the design phase, including the collection center, which was calculated in accordance with the NSR-10 regulations, encompassing a unit price analysis. After meticulous evaluation of capital expenditures (CAPEX) and operating expenses (OPEX), the alternative that best aligns with the project's main objective was chosen. This choice incurs a total cost of $13,161,578 in Colombian currency, covering both the necessary supplies and labor for the construction and operation of the chosen alternative. Subsequently, monetary calculations were performed, followed by an analysis of impacts and risks for the collection center and the alternatives, where matrices were constructed to qualify and analyze the most viable options. Additionally, the intent is to foster an initiative that safeguards this vital Colombian water body, benefiting tourists and Barranquilla residents alike